PENGEMBANGAN PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI KEGIATAN FILANTROPI (Studi Kasus Lembaga Tazakka DIII Perbankan Syariah IAIN Salatiga) - Qi Mangku Bahjatulloh (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
The purpose of this research is to analize general overview of the development economic empowerment of communities through philanthropy in Tazakka Instutition of Diploma III IAIN Salatiga. This research is field research based on case studies, the research done intensive, detailed and in-depth to an organization, institution or certain symptoms. Data analysis techniques used in this study is descriptive qualitative approach. The results showed that Tazakka institutions in carrying out its program of work in three main components: The spirit of giving (giving) spirit of giving aid to the needy, Spirit of Serving (service) .and spirit of togetherness (associate) Tazakka to carry out activities using several stages of management, the planning stage; Organizing, Monitoring movement.